Innate immunity mediator STING modulates nascent DNA metabolism at stalled forks in human cells - Lazarchuk, Pavlo; Nguyen, Vy N.; Brunon, Salomé; Pavlova, Maria N.; Sidorova, Julia M. (Frontiers in Molecular Biosciences, 2023)
The cGAS/STING pathway, part of the innate immune response to foreign DNA, can be activated by cell’s own DNA arising from the processing of the genome, including the excision of nascent DNA at arrested replication forks. Here we found that STING affects nascent DNA processing in cultured human cells. Depletion of STING suppressed and its re-expression in STING-deficient cancer cells upregulated the degradation of nascent DNA. Replication fork arrest was accompanied by the STING pathway activation, and a STING mutant that does not activate the pathway failed to upregulate nascent DNA degradation. cGAS was required for STING’s effect on degradation but this requirement could be bypassed by treating cells with a STING agonist. Cells expressing inactive STING had a reduced level of RPA on parental and nascent DNA of arrested forks and a reduced CHK1 activation compared to cells with the wild type STING. STING also affected unperturbed fork progression in a subset of cell lines. STING fractionated to nuclear fractions enriched for structural components of chromatin and nuclear envelope, and associated with chromatin of arrested replication forks. Together our findings reveal a novel connection between replication stress and innate immunity.